2020
DOI: 10.1093/comjnl/bxaa148
|View full text |Cite
|
Sign up to set email alerts
|

Deep Belief Network and Closed Polygonal Line for Lung Segmentation in Chest Radiographs

Abstract: Due to the varying appearance in the upper clavicle bone region, sharp corner at the costophrenic angle, the presence of strong edges at the rib cage and clavicle and the lack of a consistent anatomical shape among different individuals, accurate segmentation of lung on chest radiographs remains challenging. In this work, we propose a novel segmentation method for lung segmentation, containing two subnetworks, where few manually delineated points are used as the approximate initialization. The first one is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…However, these approaches were not trained in an end to end manner. In addition, Peng et al 39 proposed a twostage approach for the lung segmentation, where in the first step a Deep Belief Network and K-Nearest Neighbor is utilized to segment the lungs and then and improved principal curve and machine learning method is used for the refinement of the segmentation result. However, these types of techniques are computationally costly and necessitate a post-processing step to improve the output.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…However, these approaches were not trained in an end to end manner. In addition, Peng et al 39 proposed a twostage approach for the lung segmentation, where in the first step a Deep Belief Network and K-Nearest Neighbor is utilized to segment the lungs and then and improved principal curve and machine learning method is used for the refinement of the segmentation result. However, these types of techniques are computationally costly and necessitate a post-processing step to improve the output.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Additionally, we used 704 chest X-ray images from the Montgomery County Chest X-ray database [ 43 , 44 ] as ground truth for lung field segmentation, and 247 chest X-ray images from JSRT [ 45 , 46 ] as those for the heart. Several lung segmentation studies using these databases have been reported [ 47 49 ]. These images were resized to 224 × 224 to input the classification network.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous research ( Peng et al, 2018b ), we set 10 hidden neurons and 1,000 epochs for the FBNNL to simplify the complexity of the NN model and prevent overfitting. We used the DSC, Jaccard similarity coefficient (OMG), and accuracy (ACC) ( Peng et al, 2020 ) as the evaluation metrics. All of the ground truths were labeled and verified by three physicians.…”
Section: Methodsmentioning
confidence: 99%